Pattern of spread of African swine fever in south-western Nigeria, 1997-2005 (2007)
Geographic coordinates of selected pig farms with confirmed African swine fever (ASF) outbreaks in Ekiti, Lagos, Ogun, Ondo and Oyo States were used to create spatial models of pig farms and ASF outbreaks in southwestern Nigeria between 1997 and 2005. The probability of ASF virus-free pigs remaining in a non-infected state when located at various distances from ASF virus infected pigs was estimated. Movement of infected stock was the most important means of spreading the virus. The estimated mean duration of clinical signs prior to death was 3.4 ± 1.1 days (mean ± standard deviation); the mean convalescent period was 16.3 ± 2.3 days and the mean period of survival after full recovery was 1 084 ± 145.1 days. The continuous presence of recovered pigs in the population enables virus spread through trade and breeding. There is an urgent need for the implementation of an ASF eradication programme in Nigeria.